New RSL constraints for the Minch from OSL-dated Lateglacial shorelines - Emily Huffman; Alexander R. Simms; Tom Bradwell; Louise Best; Jeremy M. Lloyd; Sarah L. Bradley; Regina DeWitt (Quaternary Science Reviews, 2025)

P30-11 Assessment of Disposable of e-vapour products using New Approach Methodologies shows marked reductions in toxicity relative to a cigarette - O. Komini; R. Derr; I. Brandsma; R. Wieczorek; S.J. Pour; E. Trelles-Sticken; C. Kasim; K. Papikinos; M. Stevenson; L. Simms (Toxicology Letters, 2025)

P30-06 Disposable E-Vapour Products Exhibit Lower in vitro toxicological Activity Than Cigarettes - M.A. Oltean; R. Wieczorek; S.J. Pour; E.T. Sticken; K. Papikinos; C. Kasim; O. Komini; M. Stevenson; L. Simms (Toxicology Letters, 2025)

P21-01 Assessment of a range of Next Generation Nicotine products using ToxTracker® and ToxProfiler™ MAX assays reveal marked reductions in biological activity compared to a cigarette - M. Stevenson; I. Brandsma; M. Meijer; M. Rijkers; B. ter Braak; L. Wolters; E. Trelles-Sticken; R. Wieczorek; S.J. Pour; T. Evenburg; F. Chapman; L. Simms (Toxicology Letters, 2025)

Was Scotland covered by an ice sheet during Marine Isotope Stage 4? Insights from the pre‐Last Glacial Maximum marine terraces of northwest Scotland - Alexander R. Simms; Regina DeWitt; Sarah L. Bradley; Emily Huffman; Louise Best; Tom Bradwell; Jeremy M. Lloyd; Samuel B. Kachuck (Journal of Quaternary Science, 2025)
Raised shorelines provide important constraints on past sea levels, glacial isostatic adjustment (GIA), and rates and directions of vertical crustal motion. Although most raised shorelines across NW Scotland relate to post‐Last Glacial Maximum (LGM) glacial‐isostatic rebound, many undated shorelines lie above the marine limit established from isolation basins. Here, we present new optically stimulated luminescence (OSL) ages for a raised marine terrace at an elevation of 28 m in Slaggan Bay of NW Scotland. Four OSL ages suggest the feature is pre‐LGM, likely Marine Isotope Stage (MIS) 3. Global mean sea levels (GMSL) during MIS 3 are thought to have been ~40–60 m below present across most of the globe. We use a pair of GIA models to determine what ice sheet and sea‐level scenarios might provide an explanation for these anomalously high sea levels during MIS 3. Our results suggest that in the absence of tectonic activity, such high MIS 3 shorelines across NW Scotland require a MIS 4 ice sheet in Scotland, with postglacial rebound of the crustal depression following its demise during MIS 3 responsible for the elevated shoreline features at that time.

P01-04 Extracts from different next generation product platforms show less potential to induce oxidative stress than extracts from cigarettes in human coronary artery endothelial cells (HCAECs) in vitro - E. Trelles Sticken; T. Evenburg; S.J. Pour; R. Wieczorek; M. Stevenson; L. Simms (Toxicology Letters, 2024)

Early Season Wheat Response to Electrochemically Precipitated Struvite in Various Soils in the Greenhouse - Tatum Simms; Kristofor R. Brye; Trenton L. Roberts; Lauren F. Greenlee (Journal of Soil Science and Plant Nutrition, 2024)
Fertilizer-phosphorus (P) materials can be recovered from wastewater and used to supplement mined phosphate rock, where one such material is struvite [MgNH 4 PO 4 ·6(H 2 O)]. This study aimed to compare electrochemically precipitated struvite (ECST) reclaimed from synthetic wastewater to other commercial fertilizer-P sources in cultivated soils from Arkansas [silty clay loam (AR-SiCL) and silt loam (AR-SiL)], Missouri [(silt loam; MO-SiL 1 and 2)], and Nebraska [silt loam (NE-SiL) and sandy loam (NE-SL)]. A greenhouse pot study was conducted for 60 days with unvernalized wheat ( Triticum aestivum ) using five fertilizer-P sources [ECST, chemically precipitated struvite (CPST), monoammonium phosphate (MAP), triple superphosphate (TSP), and an unamended control (UC)] to evaluate treatment effects on below (BG)- and aboveground (ABG) and total dry matter (DM) and tissue-N, -P, -K, -Ca, -Mg, and -Fe uptakes. The ECST treatment produced 44 g m −2 larger ABG-DM than CPST in the AR-SiCL, but 181 g m −2 larger than the UC in the MO-SiL 1. The ECST had similar or larger nutrient uptakes than CPST, MAP, TSP, and UC. Belowground-P, -N, and -Mg uptakes for ECST were generally similar for all soil-fertilizer-P source combinations, where ECST was 0.3 to 2.6 g m −2 larger than all other fertilizer-P sources. Plant property response from ECST was generally similar to or greater than CPST, MAP, TSP, and the UC across all soils. Results suggest that ECST is a prime candidate to be used as an effective, alternative fertilizer-P source, suitable for use in wheat production across multiple soil textures.

P22-16: Heated tobacco and e-vapour products induce lower biological activity compared to cigarettes using the ToxProfiler assay - O. Komini; B.T. Braak; L. Wolters; E.T. Sticken; R. Wieczorek; S.J. Pour; F. Chapman; L. Simms; M. Stevenson (Toxicology Letters, 2023)

P14-20: Chemical and biological assessment of a Heated Tobacco Product reveals marked reductions in aerosol toxicants and in vitro toxicity compared to a combustible cigarette - R.-D. Vasile; S.J. Pour; R. Wieczorek; E.T. Sticken; V. Troude; O. Dethloff; L. Mason; L. Simms; M. Stevenson (Toxicology Letters, 2023)

P14-13: Use of Quantitative In Vitro to In Vivo Extrapolation (QIVIVE) for the assessment of Non-Combustible Next Generation products - L. Simms; M. Moreau; E. Trelles Sticken; R. Wieczorek; S.J. Pour; F. Chapman; M. Stevenson (Toxicology Letters, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The long goodbye on a disappearing, ancestral island: a just retreat from Isle de Jean Charles - Jessica R. Z. Simms; Helen L. Waller; Chris Brunet; Pamela Jenkins (Journal of Environmental Studies and Sciences, 2021)

RCAN1.4 regulates VEGFR-2 internalisation, cell polarity and migration in human microvascular endothelial cells - Ahmad F. Alghanem; Emma L. Wilkinson; Maxine S. Emmett; Mohammad A. Aljasir; Katherine Holmes; Beverley A. Rothermel; Victoria A. Simms; Victoria L. Heath; Michael J. Cross (Angiogenesis, 2017)

Nearest neighbour analysis applied to synthetic aperture radar images for the description of urban land cover and land use - Élizabeth L. Simms (International Journal of Remote Sensing, 2017)

Selection for cheating across disparate environments in the legume‐rhizobium mutualism - Stephanie S. Porter; Ellen L. Simms (Ecology Letters, 2014)
The primary dilemma in evolutionarily stable mutualisms is that natural selection for cheating could overwhelm selection for cooperation. Cheating need not entail parasitism; selection favours cheating as a quantitative trait whenever less‐cooperative partners are more fit than more‐cooperative partners. Mutualisms might be stabilised by mechanisms that direct benefits to more‐cooperative individuals, which counter selection for cheating; however, empirical evidence that natural selection favours cheating in mutualisms is sparse. We measured selection on cheating in single‐partner pairings of wild legume and rhizobium lineages, which prevented legume choice. Across contrasting environments, selection consistently favoured cheating by rhizobia, but did not favour legumes that provided less benefit to rhizobium partners. This is the first simultaneous measurement of selection on cheating across both host and symbiont lineages from a natural population. We empirically confirm selection for cheating as a source of antagonistic coevolutionary pressure in mutualism and a biological dilemma for models of cooperation.

Precision of host sanctions in the fig tree–fig wasp mutualism: consequences for uncooperative symbionts - K. Charlotte Jandér; Edward Allen Herre; Ellen L. Simms (Ecology Letters, 2012)
Host sanctions that reduce the relative fitness of uncooperative symbionts provide a mechanism that can limit cheating and thus stabilise mutualisms over evolutionary timescales. Sanctions have been demonstrated empirically in several mutualisms. However, if multiple individual symbionts interact with each host, the precision with which individual cheating symbionts are targeted by host sanctions is critical to their short‐ and long‐term effectiveness. No previous empirical study has directly addressed this issue. Here, we report the precision of host sanctions in the mutualism between fig trees and their pollinating wasps. Using field experiments and molecular parentage analyses, we show that sanctions in Ficus nymphaeifolia act at the level of entire figs (syconia), not at the level of the individual flowers within. Such fig‐level sanctions allow uncooperative wasps, which do not bring pollen, to avoid sanctions in figs to which other wasps bring pollen. We discuss the relevance of sanction precision to other mutualisms.

Transcriptomic insights into mechanisms of symbiotic cooperation - Ellen L. Simms; Stephanie S. Porter (Molecular Ecology, 2012)
Intraspecific genetic variation can affect community structure and ecosystem processes (Bolnick et al . 2011). It can also influence phenotypic expression by genotypes within other species to produce genotype‐by‐genotype ( G × G ) interaction (Falconer & Mackay 1996). Evolution of one species drives correlated evolution of others when it causes G × G for fitness (Thompson 2005). However, the mechanisms by which species interact also influence evolutionary outcomes (Kummel & Salant 2006; Golubski & Klausmeier 2010; Akçay & Simms 2011; Grman et al . 2012). To identify genes and putative functional mechanisms underlying G × G interactions, Heath et al . (2012) analysed natural variation in the symbiotic transcriptome of the mutualistic nutritional symbiosis between a legume host M edicago truncatula and the facultative endosymbiotic rhizobium S inorhizobium meliloti . Using twelve microarrays, the authors simultaneously measured host and symbiont gene expression in root nodules from four factorial pairings of host and symbiont genotypes that produced G × G in host fitness (Fig. 1, upper panel). Rhizobium gene expression was influenced by rhizobium and plant genotype and the G × G interaction (Fig. 1, lower panel), whereas plant gene expression was influenced primarily by plant genotype. The authors identified rhizobium genes that might contribute to G × G in host plant fitness. Heath et al . (2012) have moved beyond the constraints of single organism analysis towards a more realistic understanding of plants and bacteria as organisms inextricably linked with symbioses that affect even basic patterns of gene expression.

Genetic diversity and colony breeding structure in native and introduced ranges of the Formosan subterranean termite, Coptotermes formosanus - Claudia Husseneder; Dawn M. Simms; Jennifer R. Delatte; Changlu Wang; J. Kenneth Grace; Edward L. Vargo (Biological Invasions, 2012)

Disaster vulnerability and evacuation readiness: coastal mobile home residents in Florida - Margarethe Kusenbach; Jason L. Simms; Graham A. Tobin (Natural Hazards, 2010)

Inhibition of orexin-1/hypocretin-1 receptors inhibits yohimbine-induced reinstatement of ethanol and sucrose seeking in Long–Evans rats - Jemma K. Richards; Jeffrey A. Simms; Pia Steensland; Sharif A. Taha; Stephanie L. Borgland; Antonello Bonci; Selena E. Bartlett (Psychopharmacology, 2008)

No evolution of increased competitive ability or decreased allocation to defense in Melaleuca quinquenervia since release from natural enemies - Steven J. Franks; Paul D. Pratt; F. Allen Dray; Ellen L. Simms (Biological Invasions, 2008)

Nickel hyperaccumulation as an anti-herbivore trait: considering the role of tolerance to damage - Martha Palomino; Peter G. Kennedy; Ellen L. Simms (Plant and Soil, 2007)

Modelling the spread of scrapie in a sheep flock: evidence for increased transmission during lambing seasons - S. Touzeau; M. E. Chase-Topping; L. Matthews; D. Lajous; F. Eychenne; N. Hunter; J. D. Foster; G. Simm; J.-M. Elsen; M. E. J. Woolhouse (Archives of Virology, 2006)

Epistasis and genotype-environment interaction for quantitative trait loci affecting flowering time in Arabidopsis thaliana - Thomas E. Juenger; Sunak Sen; Kirk A. Stowe; Ellen L. Simms (Genetica, 2005)

Genetic Variation and Relationships of Constitutive and Herbivore-Induced Glucosinolates, Trypsin Inhibitors, and Herbivore Resistance in Brassica rapa - Donald F. Cipollini; Jeremiah W. Busch; Kirk A. Stowe; Ellen L. Simms; Joy Bergelson (Journal of Chemical Ecology, 2003)

The relative advantages of plasticity and fixity in different environments: when is it good for a plant to adjust? - Peter Alpert; Ellen L. Simms (Evolutionary Ecology, 2002)

Defining tolerance as a norm of reaction - Ellen L. Simms (Evolutionary Ecology, 2000)

Will plant vigor and tolerance be genetically correlated? Effects of intrinsic growth rate and self-limitation on regrowth - Arthur E. Weis; Ellen L. Simms; Michael E. Hochberg (Evolutionary Ecology, 2000)

Effect of seed predation on seed bank size and seedling recruitment of bush lupine ( Lupinus arboreus ) - John L. Maron; Ellen L. Simms (Oecologia, 1997)